The Value Co-Creation Process - Conceptualization and Selected Research Models - Dziewanowska , Katarzyna (Studia Oeconomica Posnaniensia, 2018)
This paper is of a theoretical nature and its purpose is to discuss the concept of value co-creation in the context of a theoretical framework and attempts to design a research tool. The first part of the paper outlines the definition of value itself and the process of its co-creation, while the second part presents selected research models that have been empirically verified. These considerations lead to a conclusion that due to intrinsic characteristics of value (subjective and perceptual nature) and the process of its co-creation, it is possible to create a general theoretical framework but not a universal measurement tool.